Development of Time Passage Media to Stimulate Symbolic Thinking and Problem Solving in 5-6 Years Old Children - Mimah, Mimah; Tabroni, Imam; Barroso, Uwe; Intes, Amina (Yayasan Adra Karima Hubbi, 2023)
Learning media is only a tool for the success of the teaching and learning process, as a component of the success of the teaching and learning process, the provision of learning media is a must. The purpose of the time passage is to introduce the concept of time, introduce the count of 1-10, and how to turn the hands of the clock. Research using research and development models from Borg & Gall. Research location at RA Ibnu Zain Respondents 4 students of Ra Ibnu Zain. The overall results of this study state that the Time Aisle Media can be used as learning media referring to the results of the validation test, the first trial pre-test 31.25% and the second trial post-test 72.5% showed there was development as expected in the time aisle media in problem solving and symbolic thinking at Ra Ibnu Zain.